The effect of exercise on depression and gut microbiota: Possible mechanisms - Mingchen Yao; Yaqi Qu; Yalin Zheng; Hao Guo (Brain Research Bulletin)
Exercise can effectively prevent and treat depression and anxiety, with gut microbiota playing a crucial role in this process. Studies have shown that exercise can influence the diversity and composition of gut microbiota, which in turn affects depression through immune, endocrine, and neural pathways in the gut-brain axis. The effectiveness of exercise varies based on its type, intensity, and duration, largely due to the different changes in gut microbiota. This article summarizes the possible mechanisms by which exercise affects gut microbiota and how gut microbiota influences depression. Additionally, we reviewed literature on the effects of exercise on depression at different intensities, types, and durations to provide a reference for future exercise-based therapies for depression.